The evolution of phototransduction and eyes - Lamb, Trevor; Arendt, Detlev; Collin, Shaun P. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2009)
Charles Darwin was acutely aware of the need to account for the evolution of ‘organs of extreme perfection’ such as the eye and, in particular, of the importance of demonstrating that numerous gradations in complexity have existed, with each intermediate stage having provided some kind of
Gesehen am 17.05.2017